Fimbrin phosphorylation by metaphase Cdk1 regulates actin cable dynamics in budding yeast - Yansong Miao (Nature Portfolio, 2016)
Metaphase cells preferentially promote actin cable assembly through cyclin-dependent kinase 1 (Cdk1) activity. Here the authors identify fimbrin as one of the main metaphase Cdk1 targets for cell cycle regulation of actin cable assembly in budding yeast.